Association of De Novo Variants With Childhood Onset Moyamoya Disease and Diffuse Occlusive Vasculopathy. - Pinard, Amelie; Fiander, Maximillian D J; Cecchi, Alana C; Rideout, Andrea L; Azouz, Mohamed; Fraser, Stuart M; McNeely, P Daniel; Walling, Simon; Novara, Sarah C; Hurst, Anna C E; Guo, Dongchuan; Parkash, Sandhya; et al. (Neurology, 2021)
OBJECTIVE: To test the hypothesis that de novo genetic variants are responsible for moyamoya disease (MMD) in children with unaffected relatives, we performed exome sequencing of 28 affected children and their unaffected parents. METHODS: Exome sequencing was performed on 28 trios of affected patients with MMD and unaffected parents. RESULTS: We identified 3 novel rare de novo variants, 1 in the RING domain and 2 in a highly conserved region distal to the RING domain (4,114-4,120). These de novo cases of MMD present at a young age with aggressive MMD and uniquely have additional occlusive vascular lesions, including renal artery stenosis. Two previously reported cases had de novo variants in the same limited region and presented young with aggressive MMD, and 1 case had narrowing of the inferior abdominal aorta. CONCLUSIONS: These results indicate a novel syndrome associated with rare variants defined by de novo mutations disrupting highly conserved amino acids in the RING domain and a discrete region distal to the RING domain delimited by amino acids 4,114 to 4,120 leading to onset of severe MMD before 3 years of age and occlusion of other arteries, including the abdominal aorta, renal, iliac, and femoral arteries.
Keywords: Adenosine Triphosphatases; Adult; Age of Onset; Aortic Diseases; Arterial Occlusive Diseases; Child, Preschool; Female; Femoral Artery; Humans; Iliac Artery; Male; Moyamoya Disease; Mutation; Renal Artery Obstruction; Ubiquitin-Protein Ligases

Inhibition of HECT E3 ligases as potential therapy for COVID-19. - Novelli, Giuseppe; Liu, Jing; Biancolella, Michela; Alonzi, Tonino; Novelli, Antonio; Patten, J J; Cocciadiferro, Dario; Agolini, Emanuele; Colona, Vito Luigi; Rizzacasa, Barbara; Giannini, Rosalinda; Bigio, Benedetta; et al. (Cell Death Dis, 2021)
SARS-CoV-2 is responsible for the ongoing world-wide pandemic which has already taken more than two million lives. Effective treatments are urgently needed. The enzymatic activity of the HECT-E3 ligase family members has been implicated in the cell egression phase of deadly RNA viruses such as Ebola through direct interaction of its VP40 Protein. Here we report that HECT-E3 ligase family members such as NEDD4 and WWP1 interact with and ubiquitylate the SARS-CoV-2 Spike protein. Furthermore, we find that HECT family members are overexpressed in primary samples derived from COVID-19 infected patients and COVID-19 mouse models. Importantly, rare germline activating variants in the NEDD4 and WWP1 genes are associated with severe COVID-19 cases. Critically, I3C, a natural NEDD4 and WWP1 inhibitor from Brassicaceae, displays potent antiviral effects and inhibits viral egression. In conclusion, we identify the HECT family members of E3 ligases as likely novel biomarkers for COVID-19, as well as new potential targets of therapeutic strategy easily testable in clinical trials in view of the established well-tolerated nature of the Brassicaceae natural compounds.
Keywords: Adult; Aged; Animals; Antiviral Agents; Chlorocebus aethiops; COVID-19; Endosomal Sorting Complexes Required for Transport; Female; Humans; Indoles; Male; Mice; Mice, Inbred BALB C; Middle Aged; Nedd4 Ubiquitin Protein Ligases; SARS-CoV-2; Spike Glycoprotein, Coronavirus; Ubiquitin-Protein Ligases; Ubiquitination; Vero Cells

Exome sequencing implicates genetic disruption of prenatal neuro-gliogenesis in sporadic congenital hydrocephalus. - Jin, Sheng Chih; Dong, Weilai; Kundishora, Adam J; Panchagnula, Shreyas; Moreno-De-Luca, Andres; Furey, Charuta G; Allocco, August A; Walker, Rebecca L; Nelson-Williams, Carol; Smith, Hannah; Dunbar, Ashley; Conine, Sierra; et al. (Nat Med, 2020)
Congenital hydrocephalus (CH), characterized by enlarged brain ventricles, is considered a disease of excessive cerebrospinal fluid (CSF) accumulation and thereby treated with neurosurgical CSF diversion with high morbidity and failure rates. The poor neurodevelopmental outcomes and persistence of ventriculomegaly in some post-surgical patients highlight our limited knowledge of disease mechanisms. Through whole-exome sequencing of 381 patients (232 trios) with sporadic, neurosurgically treated CH, we found that damaging de novo mutations account for >17% of cases, with five different genes exhibiting a significant de novo mutation burden. In all, rare, damaging mutations with large effect contributed to ~22% of sporadic CH cases. Multiple CH genes are key regulators of neural stem cell biology and converge in human transcriptional networks and cell types pertinent for fetal neuro-gliogenesis. These data implicate genetic disruption of early brain development, not impaired CSF dynamics, as the primary pathomechanism of a significant number of patients with sporadic CH.
Keywords: Brain; Cerebral Ventricles; Exome; Female; Genetic Predisposition to Disease; Humans; Hydrocephalus; Male; Mutation; Neural Stem Cells; Neurogenesis; Neuroglia; Transcription Factors; Tripartite Motif Proteins; Ubiquitin-Protein Ligases; Whole Exome Sequencing

Ari-1 Regulates Myonuclear Organization Together with Parkin and Is Associated with Aortic Aneurysms. - Tan, Kai Li; Haelterman, Nele A; Kwartler, Callie S; Regalado, Ellen S; Lee, Pei-Tseng; Nagarkar-Jaiswal, Sonal; Guo, Dong-Chuan; Duraine, Lita; Wangler, Michael F; Bamshad, Michael J; Nickerson, Deborah A; Lin, Guang; et al. (Dev Cell, 2018)
Nuclei are actively positioned and anchored to the cytoskeleton via the LINC (Linker of Nucleoskeleton and Cytoskeleton) complex. We identified mutations in the Parkin-like E3 ubiquitin ligase Ariadne-1 (Ari-1) that affect the localization and distribution of LINC complex members in Drosophila. ari-1 mutants exhibit nuclear clustering and morphology defects in larval muscles. We show that Ari-1 mono-ubiquitinates the core LINC complex member Koi. Surprisingly, we discovered functional redundancy between Parkin and Ari-1: increasing Parkin expression rescues ari-1 mutant phenotypes and vice versa. We further show that rare variants in the human homolog of ari-1 (ARIH1) are associated with thoracic aortic aneurysms and dissections, conditions resulting from smooth muscle cell (SMC) dysfunction. Human ARIH1 rescues fly ari-1 mutant phenotypes, whereas human variants found in patients fail to do so. In addition, SMCs obtained from patients display aberrant nuclear morphology. Hence, ARIH1 is critical in anchoring myonuclei to the cytoskeleton.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Animals; Aortic Aneurysm; Carrier Proteins; Cell Nucleus; Child, Preschool; Cytoskeleton; Drosophila melanogaster; Drosophila Proteins; Female; Humans; Male; Middle Aged; Mutation; Myocytes, Smooth Muscle; Pedigree; Phenotype; Ubiquitin-Protein Ligases; Young Adult

Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features. - Zhang, Jing; Gambin, Tomasz; Yuan, Bo; Szafranski, Przemyslaw; Rosenfeld, Jill A; Balwi, Mohammed Al; Alswaid, Abdulrahman; Al-Gazali, Lihadh; Shamsi, Aisha M Al; Komara, Makanko; Ali, Bassam R; Roeder, Elizabeth; et al. (Hum Genet, 2017)
Impairment of ubiquitin-proteasome system activity involving ubiquitin ligase genes UBE3A, UBE3B, and HUWE1 and deubiquitinating enzyme genes USP7 and USP9X has been reported in patients with neurodevelopmental delays. To date, only a handful of single-nucleotide variants (SNVs) and copy-number variants (CNVs) involving TRIP12, encoding a member of the HECT domain E3 ubiquitin ligases family on chromosome 2q36.3 have been reported. Using chromosomal microarray analysis and whole-exome sequencing (WES), we have identified, respectively, five deletion CNVs and four inactivating SNVs (two frameshifts, one missense, and one splicing) in TRIP12. Seven of these variants were found to be de novo; parental studies could not be completed in two families. Quantitative PCR analyses of the splicing mutation showed a dramatically decreased level of TRIP12 mRNA in the proband compared to the family controls, indicating a loss-of-function mechanism. The shared clinical features include intellectual disability with or without autistic spectrum disorders, speech delay, and facial dysmorphism. Our findings demonstrate that E3 ubiquitin ligase TRIP12 plays an important role in nervous system development and function. The nine presented pathogenic variants further document that TRIP12 haploinsufficiency causes a childhood-onset neurodevelopmental disorder. Finally, our data enable expansion of the phenotypic spectrum of ubiquitin-proteasome dependent disorders.
Keywords: Adolescent; Autism Spectrum Disorder; Carrier Proteins; Child; Child, Preschool; Cohort Studies; DNA Copy Number Variations; Facies; Female; Haploinsufficiency; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Ubiquitin-Protein Ligases

Kaufman oculo-cerebro-facial syndrome in a child with small and absent terminal phalanges and absent nails. - Kariminejad, Ariana; Ajeawung, Norbert Fonya; Bozorgmehr, Bita; Dionne-Laporte, Alexandre; Molidperee, Sirinart; Najafi, Kimia; Gibbs, Richard A; Lee, Brendan H; Hennekam, Raoul C; Campeau, Philippe M (J Hum Genet, 2017)
Kaufman oculo-cerebro-facial syndrome (KOS) is caused by recessive UBE3B mutations and presents with microcephaly, ocular abnormalities, distinctive facial morphology, low cholesterol levels and intellectual disability. We describe a child with microcephaly, brachycephaly, hearing loss, ptosis, blepharophimosis, hypertelorism, cleft palate, multiple renal cysts, absent nails, small or absent terminal phalanges, absent speech and intellectual disability. Syndromes that were initially considered include DOORS syndrome, Coffin-Siris syndrome and Dubowitz syndrome. Clinical investigations coupled with karyotype analysis, array-comparative genomic hybridization, exome and Sanger sequencing were performed to characterize the condition in this child. Sanger sequencing was negative for the DOORS syndrome gene TBC1D24 but exome sequencing identified a homozygous deletion in UBE3B (NM_183415:c.3139_3141del, p.1047_1047del) located within the terminal portion of the HECT domain. This finding coupled with the presence of characteristic features such as brachycephaly, ptosis, blepharophimosis, hypertelorism, short palpebral fissures, cleft palate and developmental delay allowed us to make a diagnosis of KOS. In conclusion, our findings highlight the importance of considering KOS as a differential diagnosis for patients under evaluation for DOORS syndrome and expand the phenotype of KOS to include small or absent terminal phalanges, nails, and the presence of hallux varus and multicystic dysplastic kidneys.
Keywords: Abnormalities, Multiple; Adult; Carrier Proteins; Child; Child, Preschool; Diagnosis, Differential; Eczema; Eye Abnormalities; Face; Facies; Female; Growth Disorders; Hand Deformities, Congenital; Humans; Intellectual Disability; Karyotype; Limb Deformities, Congenital; Male; Microcephaly; Micrognathism; Mutation; Neck; Pathology, Molecular; Sequence Analysis, DNA; Ubiquitin-Protein Ligases

RNF213 rare variants in an ethnically diverse population with Moyamoya disease. - Cecchi, Alana C; Guo, Dongchuan; Ren, Zhao; Flynn, Kelly; Santos-Cortez, Regie Lyn P; Leal, Suzanne M; Wang, Gao T; Regalado, Ellen S; Steinberg, Gary K; Shendure, Jay; Bamshad, Michael J; Grotta, James C; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Moyamoya disease (MMD) is a rare, genetically heterogeneous cerebrovascular disease resulting from occlusion of the distal internal carotid arteries. A variant in the Ring Finger 213 gene (RNF213), altering arginine at position 4810 (p.R4810K), is associated with MMD in Asian populations. However, there are a lack of data on the role of RNF213 in patients with MMD of additional ethnicities and diasporic Asian populations. We investigate the contribution of RNF213 alterations to MMD in an ethnically diverse population based in the United States. METHODS: We initially sequenced RNF213 exons 43, 44, and 45 (encoding the eponymous RING finger domain) and exon 60 (encoding p.R4810K) in 86 ethnically diverse patients with MMD. Comprehensive exome sequencing data from 24 additional patients with MMD was then analyzed to identify RNF213 variants globally. Segregation of variants with MMD and other vascular diseases was assessed in families. RESULTS: RNF213 p.R4810K was identified in 56% (9/16) of patients with MMD of Asian descent and not in 94 patients of non-Asian descent. 3.6% (4/110) of patients had variants in the exons encoding the RING finger domain. Seven additional variants were identified in 29% (7/24) of patients with MMD who underwent exome sequencing. Segregation analysis supported an association with MMD for 2 variants and a lack of association with disease for 1 variant. CONCLUSIONS: These results confirm that alterations in RNF213 predispose patients of diverse ethnicities to MMD, and that the p.R4810K variant predisposes individuals of Asian descent in the United States to MMD.
Keywords: Adenosine Triphosphatases; Adolescent; Adult; Child; Cohort Studies; Ethnic Groups; Female; Genetic Variation; Humans; Male; Moyamoya Disease; Population Surveillance; Ubiquitin-Protein Ligases; Young Adult